Siaran Budaya Sebagai Upaya Melestarikan KebudayaanDaerah Melalui Program Acara di TVRI D.I.Yogyakarta - Dewi, Mutia (KOMUNITAS, 2014)
Television is one of the mass media which has the power to influence the public through broadcast  programs.  Television  power  be  able  to  change  the  behavior  and  culture  through entertainment  or  violence  program.  Therefore  dominating  entertainment  programs  and  shows violence  on  television,  this  study  wanted  to  see  how  the  efforts  to  be  made  by  TVRI  D.I. Yogyakarta as public broadcasters to preserve localculture through the production of cultural programs by category, as well as supporting factorsand obstacles in an effort preserving local culture through broadcasting programs. The data obtained through interviews, documentation and observation. The results show the percentage ofprograms with cultural themes comprising approximately  14.21%  of  the  pangkur  jenggleng,  obrolan  angkringan,  cangkriman, karangtumaritis, ketoprak, keroncong, and konser jawa.